Hadith-Based Islamic Education and Strengthening Ecological Awareness among Santri - Bahrum Subagiya (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2026)
Environmental degradation has become a pressing global concern, requiring religious education institutions to play a more active role in fostering ecological responsibility. This research aims to understand the meaning of the term santri in the hadith about planting trees and its implications for ecological awareness at Pesantren Ibnu Jauzy in Bogor. Using a qualitative, phenomenological approach, this study explores santri's subjective experience in understanding the ecological values contained in the hadith. Data were collected through in-depth interviews, participatory observations, and documentation of pesantren activities related to the environment. The data were analyzed using thematic analysis, involving data reduction, coding, categorization, and interpretation to identify patterns of meaning construction and ecological practice. The study's results show that santri's theoretical understanding of hadiths on tree planting still needs improvement. Still, their ecological practices in daily life have already been put into practice. Their ecological awareness is reflected in reforestation activities around the pesantren, the creation of biopore holes that produce organic fertilizer, and the use of food waste as fish feed. This shows that ecological awareness can arise from community culture, but will have a greater impact if it is based on religious awareness derived from Islamic teachings.